2021
DOI: 10.1101/2021.07.29.454328
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automatic calibration of a functional-structural wheat model using an adaptive design and a metamodelling approach

Abstract: - Background and Aims Functional-structural plant models are increasingly being used by plant scientists to address a wide variety of questions. However, the calibration of these complex models is often challenging, mainly because of their high computational cost. In this paper, we applied an automatic method to the calibration of WALTer: a functional-structural wheat model that simulates the plasticity of tillering in response to competition for light. - Methods We used a Bayesian calibration method to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(39 reference statements)
1
2
0
Order By: Relevance
“…However, it is expected that both sowing density and the proportions of the two cultivars in mixture should have an impact on the results (Grace and Tilman, 1990). Moreover, the sowing density has been identified, as expected, as one of the most influential inputs in WALTer (Lecarpentier et al, 2019;Blanc et al, 2021), supporting the interest in exploring variations of this parameter. FSPMs are particularly adapted to explore these agricultural practices (Evers et al, 2019;Gaudio et al, 2019).…”
Section: Toward the Identification Of Assembly Rulessupporting
confidence: 65%
See 1 more Smart Citation
“…However, it is expected that both sowing density and the proportions of the two cultivars in mixture should have an impact on the results (Grace and Tilman, 1990). Moreover, the sowing density has been identified, as expected, as one of the most influential inputs in WALTer (Lecarpentier et al, 2019;Blanc et al, 2021), supporting the interest in exploring variations of this parameter. FSPMs are particularly adapted to explore these agricultural practices (Evers et al, 2019;Gaudio et al, 2019).…”
Section: Toward the Identification Of Assembly Rulessupporting
confidence: 65%
“…Nevertheless, as for any modeling exercise (Passioura, 1996), our study presents some approximations that must be considered when interpreting the results. Indeed, even though WALTer allows for a realistic simulation of the tillering dynamics in response to competition for light (Lecarpentier et al, 2019;Blanc et al, 2021), some of the underlying hypotheses of the model should be mentioned. First of all, light is the only environmental factor considered in the model: water and nutrients (nitrogen, phosphorus, potassium, sulfur.…”
Section: Fspm As a Tool To Study Heterogeneous Canopiesmentioning
confidence: 99%
“…In a climate impact study of Ben Touhami and Bellocchi [ 139 ] it was found that the inclusion of prior information was beneficial for uncertainty estimates, even if these information came from different climate conditions. Blanc et al [ 140 ] point out that a pitfall of Bayesian model calibration for functional-structural plant models is that with transferring uncertainties in model parameters repetitive simulation runs are necessary for robust estimates of output variables. To address this, they propose a surrogate modeling approach to substitute time consuming FSP model simulations with simpler models, such as Kriging models.…”
Section: Appendix A1 More On Phenology Modelingmentioning
confidence: 99%